Undifferentiated embryonal sarcoma of the liver in an adult patient: Case report - Umut VAROL; Burçak KARACA; Uğur MUSLU; Latife DOĞANAY; Mustafa DEĞİRMENCİ; Rüçhan USLU; Erdem GÖKER (Turkish Journal of Gastroenterology, 2019)
-